Science and judicial reasoning : the legitimacy of international environmental adjudication - Sulyok, Katalin, 1986- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"Science often entails connotations of 'objectivity', 'certainty', and the capability to discover the 'factual truth'. Judicial decisions, in turn, are routinely associated with resolving disputes in a 'final', 'neutral', and 'authoritative' way. Yet international environmental adjudication, where scientific and legal authority get entangled with each other, suggests that neither science nor law can fully live up to these idealized expectations. What happens if science and law yield competing narratives as to the factual basis of a dispute? Who could and should resolve their conflict and how, based on what benchmarks? Would the uncertain, probabilistic nature of scientific input diminish the authority of a legal judgment based upon it?"--
Introduction to a comparative study on judicial engagement with science -- The rules of judicial engagement with science : a three-fold challenge -- Judicial engagement with science in the environmental case : law of the International Court of Justice -- Science in the practice of inter-state arbitral tribunals -- Science in the environmental jurisprudence of regional human rights courts -- Scientific claims before the WTO -- Science in the practice of investment arbitral tribunals -- Science appears before the international tribunal for the Law of the Sea -- Trends in judicial engagement with science : a comparative assessment -- Science and the legitimacy of judicial reasoning.
Includes bibliographical references (page : 371 - 390) and index.
Keywords: Environmental law, International; Judicial process; Science and law; Arbitration (International law)